An Economics Approach to Language Policy and Linguistic Justice - Bengt-Arne Wickström; Torsten Templin; Michele Gazzola (Center for Economic Studies and ifo Institute (CESifo), 2017)
The essay gives an overview of how language planning and language policy can be motivated and analyzed by economic methods. It is discussed what type of value language-related goods possess and what type of goods they are. Properties like degrees of rivalry, exclusion, and shielding and how they can justify language planning are treated. A cots-benefit approach to language planning is suggested and critically discussed. Especially the structure of costs and its significance for the cost-benefit analysis is scrutinized. It is shown that the cost structure has some clear implications for practical language planning. Finally, the focus is directed towards distributional issues related to language policy.
Keywords: D61; 330; language planning; language policy; cost-benefit analysis